2023
DOI: 10.1002/anie.202303032
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Cyclopropanes from Carbon Pronucleophiles and Alkenes

Abstract: Cyclopropanes are desirable structural motifs with valuable applications in drug discovery and beyond. Established alkene cyclopropanation methods give rise to cyclopropanes with a limited array of substituents, are difficult to scale, or both. Herein, we disclose a new cyclopropane synthesis through the formal coupling of abundant carbon pronucleophiles and unactivated alkenes. This strategy exploits dicationic adducts derived from electrolysis of thianthrene in the presence of alkene substrates. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 96 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…In 2023, Wickens and co‐workers reported a formal alkene cyclopropanation protocol that leverages the reactivity of thianthrenium intermediates (Scheme 12). [49] In this report, treatment of electrochemically‐generated thianthrenium electrophiles with diverse carbon pronucleophiles and a base (Cs 2 CO 3 ) afforded substituted cyclopropane products. Of note, basic heterocycles, such as pyridines and pyrimidines, served as suitable secondary electron‐withdrawing groups on the carbon coupling partner.…”
Section: Alkenes As Vicinal Dication Equivalentsmentioning
confidence: 89%
See 1 more Smart Citation
“…In 2023, Wickens and co‐workers reported a formal alkene cyclopropanation protocol that leverages the reactivity of thianthrenium intermediates (Scheme 12). [49] In this report, treatment of electrochemically‐generated thianthrenium electrophiles with diverse carbon pronucleophiles and a base (Cs 2 CO 3 ) afforded substituted cyclopropane products. Of note, basic heterocycles, such as pyridines and pyrimidines, served as suitable secondary electron‐withdrawing groups on the carbon coupling partner.…”
Section: Alkenes As Vicinal Dication Equivalentsmentioning
confidence: 89%
“…This initial report indicated that the formal substitution of the dicationic adducts could occur by either direct substitution or an elimination‐conjugate addition pathway that proceeds via an alkenylthianthrenium intermediate. Authors from the same research group in a later report (see below) settled on the elimination‐based alkenylthianthrenium pathway as the more likely mechanism [49] …”
Section: Alkenes As Vicinal Dication Equivalentsmentioning
confidence: 99%
“…First, electron-deficient boron atoms 40,41 should effectively promote the through-space conjugation of the lone pair electrons on the PU chains. At the same time the cyclopropyl ring can control the 3D structural rigidity of PU molecules 42–44 and limit the intramolecular rotation and vibration of the PU chains, promoting the formation of clusters and the spatial conjugation of electron clouds, giving rise to luminescence. Moreover, the stability of triplet excitons is enhanced which should prolong the phosphorescence lifetime, by analogy with aromatic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these data do not exclude the possibility that transient thianthrenium electrophiles may be generated during allylic amination in low steady-state concentrations. With these initial mechanistic insights, we opted to skip the highly exothermic elimination step (Δ H = −27.0 kcal/mol; see Figure S78) of dicationic precursors to simplify the reaction conditions. , Thus, we conducted our experimental investigations using alkenylthianthrenium salt 3 (Scheme ).…”
mentioning
confidence: 99%